1990
DOI: 10.1111/j.1600-0722.1990.tb00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral electrochemical action after soft drink rinsing and consumption of sweets

Abstract: – The aim of this study was to investigate the influence of pH changes in dental plaque and saliva on the magnitude of the galvanic current created when amalgam restorations make contact in the oral cavity. Ten persons with 46 contacts between amalgam fillings in all participated in the experiments. Potential, polarization, and pH measurements were performed before and after Coca‐Cola and orange juice rinsing and intake of sweets, which were used as test products. Distilled water was used as a control. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Since smokers have lower salivary pH and buffering capacity than nonsmokers (16), only nonsmokers were recruited for the present study. Additionally, since some foods and drinks affect salivary pH (17), we requested that all subjects allowed their mouths to fill with saliva and then swallow it, so that saliva sampled subsequently would be fresh. During the daytime, subjects were required to measure salivary pH several times, and to avoid sampling for a 1-h period after eating or drinking.…”
Section: Monitoring Of Phmentioning
confidence: 99%
“…Since smokers have lower salivary pH and buffering capacity than nonsmokers (16), only nonsmokers were recruited for the present study. Additionally, since some foods and drinks affect salivary pH (17), we requested that all subjects allowed their mouths to fill with saliva and then swallow it, so that saliva sampled subsequently would be fresh. During the daytime, subjects were required to measure salivary pH several times, and to avoid sampling for a 1-h period after eating or drinking.…”
Section: Monitoring Of Phmentioning
confidence: 99%
“…However, this pH drop was not below the critical pH for both enamel and dentin. The variation in the response among different groups of biscuit can be attributed to the differences in their composition 17 and the free sugar content. All the five groups of biscuits contained added sugar with highest in glucose biscuit group (25.5 g) followed by chocolate biscuit (7 g), cream biscuit (6 g), salt biscuit (3 g) and least in oats biscuit (1 g) as mentioned in the pack.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that packaged fruit juices and fruit-based carbonated beverages, having increased buffering capacities, may instigate an elongated drop in oral pH. 17 Although the quantity of acidic beverages normally ingested by children may be negligible, the presence of inability to clear retentive substrate, immature enamel, and inadequate neuromuscular coordination makes them more prone to dental erosion.…”
Section: Discussionmentioning
confidence: 99%